Validation of the Kazakh-language version of the World Health Organization's WHOQOL-BREF questionnaire on the quality of life among the elderly population of Aktobe city - Nurgul Abenova; Akbayan Imanbayeva; Bibigul Karimsakova; Inkara Essengalyeva (National Scientific Medical Center, 2021)
Introduction. In Kazakhstan, as the phenomenon of population aging becomes more and more relevant, an increasing number of researchers in the field of medicine are studying health-related problems that arise at this age. During these studies, many scientists are wondering: how to accurately measure the quality of life of older people? In our country, the most used tools for conducting this assessment are the SF-36 questionnaire, while the widely used worldwide tools WHOQOL-100 and its short version WHOQOL-BREF are rarely evaluated and used in the Republic of Kazakhstan. Thus, the aim of this study was to determine the psychometric properties of the Kazakh-language version of the World Health Organization's Short Quality of Life Questionnaire (WHOQOL-BREF) in a pilot study. Material and methods. The WHOQOL-BREF questionnaire was subjected to translation procedures according to the instructions of WHOQOL (WHO) and a pilot study was conducted in a group of elderly respondents (>60 years old) living in the city of Aktobe. The WHOQOL-BREF questionnaire consists of 26 questions, which are divided into 4 areas (physical health, emotional health, social factors, environment). The reliability and validity of the questionnaire was evaluated with the determination of the Alpha-Cronbach's index, as well as the assessment of the intra-class correlation (ICC). The statistical significance was set at 0.05. The software package SPSS v. 10.0 was used for the analysis. Results. The average age of the participants was 67.3±5.03 years, and the overall WHOQOL-BREF score was 76.02 ±11.86. Overall, 60% of the participants were women. The alpha values for each of the spheres and the overall index (> 0.70) and the overall correlation of the elements were satisfactory. The confirmatory analysis of the intra-class correlation showed high ICC values (more than 0.74) for each of the spheres. Conclusion. The psychometric properties of the Kazakh version of WHOQOL-BREF were acceptable.